Boosting Perovskite Solar Cells Efficiency and Stability: Interfacial Passivation of Crosslinked Fullerene Eliminates the "Burn‐in" Decay. Issue 2 (4th December 2022) - Ding, Changzeng; Yin, Li; Wang, Jinlong; Larini, Valentina; Zhang, Lianping; Huang, Rong; Nyman, Mathias; Zhao, Liyi; Zhao, Chun; Li, Weishi; Luo, Qun; Shen, Yanbin; et al.
Abstract: Perovskite solar cells (PSCs) longevity is nowadays the bottleneck for their full commercial exploitation. Although lot of research is ongoing, the initial decay of the output power – an effect known as "burn‐in" degradation happening in the first 100 h – is still unavoidable, significantly reducing the overall performance (typically of >20%). In this paper, the origin of the "burn‐in" degradation in n‐i‐p type PSCs is demonstrated that is directly related to Li + ions migration coming from the SnO2 electron transporting layer visualized by time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) measurements. To block the ion movement, a thin cross‐linked [6, 6]‐phenyl‐C61‐butyric acid methyl ester layer on top of the SnO2 layer is introduced, resulting in Li + immobilization. This results in the elimination of the "burn‐in" degradation, showing for the first time a zero "burn‐in" loss in the performances while boosting device power conversion efficiency to >22% for triple‐cation‐based PSCs and >24% for formamidinium‐based (FAPbI3 ) PSCs, proving the general validity of this approach and creating a new framework for the realization of stable PSCs devices. Abstract : Li + ion migration induced "burn‐in" degradation in n‐i‐p type perovskite solar cells is reported. To block the Li + ion movement, a thin cross‐linked [6, 6]‐phenyl‐C61‐butyric acid methyl ester layer is introduced on top of the SnO2 layer, resulting in Li + immobilization. Finally, the efficiency and stability are significantly improved.